2015
DOI: 10.12973/eurasia.2016.1523a
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Secondary Mathematics Teachers’ Behaviors in the Proving Process

Abstract: Pre-service secondary mathematics teachers' (PSMTs) understanding and ability of constructing a proof is not only important for their own learning process, but also important for these PSMTs to help their future students learn how to do proofs. Therefore, this study is focused on and explains PSMTs' behaviors that they revealed throughout the proving process of a proposition. In this qualitative case study, the participants were fifteen volunteer PSMTs from a public university in Turkey. The participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Fourth, Ug ǔrel's [20] study on pe-service secondary teachers' behaviors in the proving process is examined. The major goal of the study was to generate insights about the kinds of proof behaviours revealed by pre-service teachers when they proved a given proposition.…”
Section: Critical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, Ug ǔrel's [20] study on pe-service secondary teachers' behaviors in the proving process is examined. The major goal of the study was to generate insights about the kinds of proof behaviours revealed by pre-service teachers when they proved a given proposition.…”
Section: Critical Reviewmentioning
confidence: 99%
“…The major goal of the study was to generate insights about the kinds of proof behaviours revealed by pre-service teachers when they proved a given proposition. Ug ǔrel [20] studied 15 volunteer pre-service teachers of whom 5 were male and 10 were female. To solicit data each pre-service teacher was asked to prove a given proposition on the chalkboard by thinking aloud as the student teacher presented the proof.…”
Section: Critical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main objectives of mathematics teaching is for students to like mathematics, enjoy mathematics and have confidence in their mathematical abilities (Cantürk, 2006). Since attitude is a tendency formed in the previous step before a behavior is exhibited, attitudes developed negatively towards mathematics turn into behaviors by being influenced by other reasons one step later and they constitute an obstacle in achieving success in mathematics teaching (Uğurel & Moralı, 2006). Attitude towards linear algebra course can be expressed as all feelings such as whether they like linear algebra course or not, their self-confidence towards the course, their enjoyment of linear work and their confidence in their abilities.…”
Section: Introductionmentioning
confidence: 99%
“…al. [5]. Hence, if undergraduate mathematics education students do not master the concept of mathematical proof adequately they are less likely to develop it in their own learners in a persuasive manner.…”
mentioning
confidence: 99%